Regulation of Macrophage Metabolism by Traditional PlantBased Extracts Under High-Glucose and Inflammatory Stress: An in vitro study (Comprehensive Journal of Science, 2025)
Background: Chronic inflammation associated with diabetes often lead to abnormal lipidlevels and oxidative stress, both of which play a key role in the progression of metabolicsyndrome. Researchers continue to investigate medications aimed at preventing ormanaging diabetes-related complications. This study investigated the therapeutic potential ofthree herbal extracts by assessing their impact on macrophage oxidative bioactive markerexpression in metabolic disorders and comparing the results with those of conventionalWestern medicine. Method: In this study, the following inhibited concentrations wereapplied to treat LPS-stimulated inflammation in high-glucose mimic cell cultures: Artemisiaafra (200 µg/ml), Cinnamon verum (250 µg/ml), Fenugreek (2500 µg/ml), and metformin(200 µg/ml). Results: LPL is significantly overexpressed, while SOD-2 activity issuppressed in the presence of high glucose, both with and without stimulation by LPSactivated macrophage cells. A. afra and C. verum extracts promoted cell growth under highglucose conditions more effectively than Fenugreek and metformin. Cinnamon verumsignificantly enhances the antioxidant enzyme SOD-2 and effectively downregulates theLPL enzyme under high glucose conditions, both in the presence and absence of stimulation.Compared to Artemisia afra, fenugreek, or metformin. In conclusion: These herbs helpregulate metabolic markers in diabetic patients may help prevent diabetes progression, treatatherosclerosis, and manage chronic inflammation while supporting glucose control. Futureinvestigations are essential to identify and understand the bioactive molecules in these herbaltherapies involved in this protocol.
Keywords: Diabetes mellitus, High glucose, Metabolic syndrome, Artemisia afra, Cinnamon verum, Fenugreek., Inflammation